(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
This research paper will begin with philosophically exploring the saying The Researcher You Are Is The Person You Are. This provide an insight on the views and the perspectives of the researcher on the research as a subject. Subsequently, the other contents of the paper are divided into two major sections. The first section discusses the Qualitative and Quantitative philosophical and theoretical debates in contemporary educational research; Qualitative and Quantitative approaches in educational research; Objectivity and Subjectivity in educational research; Links between Data Collection and Data Analysis in educational research. The second part of the paper discussed the action research in education and the reflection of the person you are is the researcher you are in educational research settings. Finally, the paper conclude that there is no single formula when it comes to conducting research in education, each and every researcher regardless of his or her area of study would always be conducting research based on what he or she thinks and deems is the best research paradigm and method to adopt. However, there are some confident guiding principles that their application guarantee effectiveness to a certain degree in educational research.